Strategies for modelling BRT massive transportation systems-transmilenio case (2016)
Recently, the bus rapid transit (BRT) systems have been implemented around the world as an efficient and Iow cost mass public transportation alternative. This work intends to draw general guidelines for complete transportation systems modelling that seek to diagnose and improve performance, as well as to present auxiliary models needed for transportation systems modelling. Users and buses logic within a BRT station are described using a unique cost function for each user and a "Lego Approach" is implemented for creating any kind of BRT system model. Using the methodology described in this research a valid simulation model of the complete Transmilenio BRT is built and a heuristic methodology for obtaining good feasible buses frequency assignment is proposed